EMAP: A 3-D, FINITE ELEMENT MODELING CODE FOR ANALYZING TIME-VARYING ELECTROMAGNETIC FIELDS - Hubing, Todd (Applied Computational Electromagnetics Society Journal (ACES), 2022)
No Abstract provided. [Vol. 8, No. 1, (1993), Special Issue on Computer Applications in Electromagnetics Education, pp 116-124]